Lymphocytes transiently expressing virus-specific T cell receptors reduce hepatitis B virus infection - Kah, Janine (J Clin Invest, 2017)
Adoptive transfer of T cells engineered to express a hepatitis B virus–specific (HBV-specific) T cell receptor (TCR) may supplement HBV-specific immune responses in chronic HBV patients and facilitate HBV control. However, the risk of triggering unrestrained proliferation of permanently engineered T cells raises safety concerns that have hampered testing of this approach in patients. The aim of the present study was to generate T cells that transiently express HBV-specific TCRs using mRNA electroporation and to assess their antiviral and pathogenetic activity in vitro and in HBV-infected human liver chimeric mice. We assessed virological and gene-expression changes using quantitative reverse-transcriptase PCR (qRT-PCR), immunofluorescence, and Luminex technology. HBV-specific T cells lysed HBV-producing hepatoma cells in vitro. In vivo, 3 injections of HBV-specific T cells caused progressive viremia reduction within 12 days of treatment in animals reconstituted with haplotype-matched hepatocytes, whereas viremia remained stable in mice receiving irrelevant T cells redirected toward hepatitis C virus–specific TCRs. Notably, increases in alanine aminotransferase levels, apoptotic markers, and human inflammatory cytokines returned to pretreatment levels within 9 days after the last injection. T cell transfer did not trigger inflammation in uninfected mice. These data support the feasibility of using mRNA electroporation to engineer HBV TCR–redirected T cells in patients with chronic HBV infection.